2018
DOI: 10.1038/s41419-018-1096-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of transcriptomics and clinical data uncovers the tumor-suppressive activity of MITF in prostate cancer

Abstract: The dysregulation of gene expression is an enabling hallmark of cancer. Computational analysis of transcriptomics data from human cancer specimens, complemented with exhaustive clinical annotation, provides an opportunity to identify core regulators of the tumorigenic process. Here we exploit well-annotated clinical datasets of prostate cancer for the discovery of transcriptional regulators relevant to prostate cancer. Following this rationale, we identify Microphthalmia-associated transcription factor (MITF) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Additional personalized cutoffs can be established through the access to raw data files provided in the custom analysis. Indeed, the inverse association of MITF to disease-free survival was significant in two out of three datasets analyzed when the patients within the first quartile of gene expression were compared with the rest of the cohort (18). Of note, in support of the possibility of monitoring the expression of LINCs in CANCERTOOL, Supplementary Fig.…”
Section: Basic Analysesmentioning
confidence: 76%
See 2 more Smart Citations
“…Additional personalized cutoffs can be established through the access to raw data files provided in the custom analysis. Indeed, the inverse association of MITF to disease-free survival was significant in two out of three datasets analyzed when the patients within the first quartile of gene expression were compared with the rest of the cohort (18). Of note, in support of the possibility of monitoring the expression of LINCs in CANCERTOOL, Supplementary Fig.…”
Section: Basic Analysesmentioning
confidence: 76%
“…1, we depict an illuminating example of the analysis of a gene identified as potential regulator of prostate cancer biology using this type of Basic Analyses tool. This gene was subsequently corroborated as an important player in this tumor type (18). The Representative heatmap provided by CANCERTOOL for the correlation analyses of MITF against the indicated genes in multiple prostate cancer datasets.…”
Section: Basic Analysesmentioning
confidence: 97%
See 1 more Smart Citation
“…CRYAB may be regulated by Ets1 (breast cancer) 47 , KLF4 (osteosarcoma) 48 , HSFI (hepatocellular carcinoma) 49 . Valcarcel-Jimenez et al 50 found MITF exerted tumor-suppressive activity in PCa, and CRYAB was the direct target of MITF. However, there was a complex regulatory network between molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MITF is involved in cell cycle regulation [ 11 , 12 ], cell survival [ 13 , 14 ], cell differentiation [ 15 ], and cell migration [ 16 , 17 ]. In addition to melanoma, several tumors are associated with the dysregulation of the MITF gene, including renal cell carcinoma [ 18 ], clear cell sarcoma [ 19 ], prostate cancer [ 20 ], and chronic myeloid leukemia [ 21 ], but there are no reports of its involvement in OvCa.…”
Section: Introductionmentioning
confidence: 99%